ANALISIS ECONOMIC VALUE ADDED (EVA), FINANCIAL VALUE ADDED (FVA) DAN MARKET VALUE ADDED (MVA) SEBAGAI ALAT UKUR KINERJA KEUANGAN - Ayu Cahyandari; Hamzah Fansuri Yusuf; Lia Rachmawati (Universitas Muhammadiyah Jember, 2021)
This study aims to determine and analyze the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) based on the (EVA), (FVA) and (MVA) methods in 2015 – 2019. This type of research is a quantitative descriptive study, and the population in this study, namely all manufacturing companies listed on the Indonesia Stock Exchange (IDX). Hypothesis testing is a non-parametric test analysis, namely the Kruskal Wallis test. Based on the results of the calculations and analysis carried out, it is stated that the (EVA), (FVA) and (MVA) Manufacturing Companies during the period 2015 – 2019 as a whole show positive numbers which can be said that the financial performance of manufacturing companies good.